E-commerce & implications for Indian business - Mehra, Vikas (2000)
E-Commerce is boundaryless and has become a potent force for conducting national and international business. While in the developed world it has already been granted recognition as the future mode of doing commerce, India lags behind in this aspect. This paper seeks to explain the concept of E-commerce and its implications specifically with respect to the Indian situation. - Reproduced
Keywords: Enterprises; Information technology; Electronic commerce